Predicting death over 8 years in a prospective cohort of HIV-infected women: the Women's Interagency HIV Study. Issue 6 (30th June 2017) - Gustafson, Deborah R; Shi, Qiuhu; Holman, Susan; Minkoff, Howard; Cohen, Mardge H; Plankey, Michael W; Havlik, Richard; Sharma, Anjali; Gange, Stephen; Gandhi, Monica; Milam, Joel; Hoover, Donald R
Abstract : Objectives: Predicting mortality in middle-aged HIV-infected (HIV+) women on antiretroviral therapies (ART) is important for understanding the impact of HIV infection. Several health indices have been used to predict mortality in women with HIV infection. We evaluated: (1) an HIV biological index, Veterans Aging Cohort Study (VACS); (2) a physical index, Fried Frailty Index (FFI); and (3) a mental health index, Center for Epidemiologic Studies-Depression (CES-D). Proportional hazards regression analyses were used to predict death and included relevant covariates. Design: Prospective, observational cohort. Setting: Multicentre, across six sites in the USA. Participants: 1385 multirace/ethnic ART-experienced HIV+ women in 2005. Primary and secondary outcomes: All deaths, AIDS deaths and non-AIDS deaths up to ~8 years from baseline. Results: Included together in one model, VACS Index was the dominant, significant independent predictor of all deaths within 3 years (HR=2.20, 95% CI 1.83, 2.65, χ 2 =69.04, p<0.0001), and later than 3 years (HR=1.55, 95% CI 1.30, 1.84, χ 2 =23.88, p<0.0001); followed by FFI within 3 years (HR=2.06, 95% CI 1.19, 3.57, χ 2 =6.73, p=0.01) and later than 3 years (HR=2.43, 95% CI 1.58, 3.75, χ 2 =16.18, p=0.0001). CES-D score was not independently associated with mortality. Conclusions and relevance: This is the first simultaneous evaluation of three common health indices in HIV+ adults. Indices reflecting physical and biological ageing were associated with death.